Kinin B2 Receptor Activation Prevents the Evolution of Alzheimer's Disease Pathological Characteristics in a Transgenic Mouse Model - Marielza Andrade Nunes; Mariana Toricelli; Natalia Mendes Schöwe; Helena Nascimento Malerba; Karis Ester Dong-Creste; Daniela Moura Azevedo Tuma Farah; Katia De Angelis; Maria Claudia Irigoyen; Fernand Gobeil; Tânia Araujo Viel; Hudson Sousa Buck (MDPI AG, 2020)
Background: Alzheimer's disease is mainly characterized by remarkable neurodegeneration in brain areas related to memory formation. This progressive neurodegeneration causes cognitive impairment, changes in behavior, functional disability, and even death. Our group has demonstrated changes in the kallikrein-kinin system (KKS) in Alzheimer's disease (AD) experimental models, but there is a lack of evidence about the role of the KKS in Alzheimer's disease. Aim: In order to answer this question, we evaluated the potential of the kinin B2 receptors (BKB2R) to modify AD characteristics, particularly memory impairment, neurodegeneration, and Aβ peptide deposition. Methods: To assess the effects of B2, we used transgenic Alzheimer's disease mice treated with B2 receptor (B2R) agonists and antagonists, and performed behavioral and biochemical tests. In addition, we performed organotypic hippocampal culture of wild-type (WT) and transgenic (TG) animals, where the density of cytokines, neurotrophin BDNF, activated astrocyte marker S100B, and cell death were analyzed after treatments. Results: Treatment with the B2R agonist preserved the spatial memory of transgenic mice and decreased amyloid plaque deposition. In organotypic hippocampal culture, treatment with B2R agonist decreased cell death, neuroinflammation, and S100B levels, and increased BDNF release. Conclusions: Our results indicate that the kallikrein-kinin system plays a beneficial role in Alzheimer's disease through B2R activation. The use of B2R agonists could, therefore, be a possible therapeutic option for patients diagnosed with Alzheimer's disease.